Settlement Analysis of Follow-up Results of the Examination of the Auditor West Sumbawa District Inspectorates - Harinurhady, Agus; Rifa'i, Ahmad; Alamsyah, Alamsyah (Jurnal Economia, 2017)
Abstract: Settlement Analysis of Follow-up Results of the Examination of the Auditor West Sumbawa District Inspectorates. This research examined from the perspective of an auditee using a qualitative approach, case study method, and technique of thematic analysis. The phenomenon of this research report is based on the results of monitoring yearly by the monitoring unit of the Inspectorate of Western Sumbawa district that shows the existence of the fact that the completion of follow-up there still are in the process and not to be follow up. The study results found a lack of communication on the work unit management level of West Sumbawa Regency and still lack the human resources (HR) are competent, so the completion of follow-up has not reached its full potential as evidenced by the completion status still has not been and/or not acted upon. For the future so that the head/leader of the work unit, which has a commitment to the quest of completion can seek better communication and involving all the components in the organization by forming a pattern of relationship tasks. Keywords: auditing, examination, follow-up, monitoring, supervision.Abstrak: Analisis Penyelesaian Tindak Lanjut Hasil Pemeriksaan Auditor Inspektorat Kabupaten Sumbawa Barat.  Penelitian ini dikaji dari perspektif auditi dengan menggunakan pendekatan kualitatif, metode studi kasus dan teknik analisis tematik. Fenomena penelitian ini berdasarkan pada laporan hasil pemantauan tahunan oleh unit pemantauan Inspektorat Kabupaten Sumbawa Barat yang menunjukkan adanya fakta bahwa penyelesaian tindak lanjut masih ada yang berstatus dalam proses dan belum ditindaklanjuti. Hasil penelitian menemukan kurangnya komunikasi pada tingkatan manajemen SKPD Kabupaten Sumbawa Barat dan masih kurangnya Sumber Daya Manusia (SDM) yang kompeten, sehingga penyelesaian tindak lanjut belum tercapai secara maksimal yang dibuktikan dengan masih adanya status penyelesaian yang belum dan/atau tidak ditindaklanjuti. Untuk ke depannya agar kepala/pimpinan SKPD yang secara umum memiliki komitmen dalam upaya penyelesaian dapat mengupayakan komunikasi yang lebih baik dan melibatkan semua komponen dalam organisasi dengan membentuk pola hubungan tugas. Kata Kunci: audit, pemeriksaan, pengawasan, pemantauan, tindak lanjut.